Report from the Workshop on the Development of the Weddell Sea - Dronning Maud Land Regional Working Group SOOS - de Steur, Laura; Gutt, Julian; Moreau, Sebastien ([Zenodo], 2009)
This report summaries the first workshop of the Southern Ocean Observing System (SOOS) Weddell Sea and Dronning Maud Land (WS-DML) Regional Working Group held Tromsø, Norway, in January 2019.
Keywords: Dronning Maud Land; Sørishavet; geofysikk; geologi; konferanse; symposium

Observasjoner av atmosfæriske parametere ved Troll-stasjonen i Antarktis - forskning og overvåkning basert på lange tidsserier. Fase 1 (2005/06) - NFR/NARE prosjekt 168908/S30 - Hansen, Georg Heinrich; Aspmo, Katrine; Berg, Torunn; Edvardsen, Kåre; Fiebig, Markus; Kallenborn, Roland; Lunder, Chris Rene; Nilsen, Tore; Schmidbauer, Norbert; Solberg, Sverre; Stebel, Kerstin; Wasseng, Jan; et al. (NILU, 2007)
Fra årsskifte 2006/2007 har den norske Antarktisstasjonen Troll (72º S, 2º E, 1270 m.o.h.) i Dronning-Maud-Land vært en helårsbemannet forsknings-, overvåkings- og servicestasjon. Dette åpnet for muligheten til å gjennomføre kontinuerlige målinger av en rekke viktige atmosfæriske parametre. I februar 2007 ble den nye NILU-atmosfære målestasjonen på Troll satt i gang. Måleprogrammet omfatter optiske, fysiske og kjemiske egenskaper av aerosoler, totalozon og UV-stråling, uorganisk og organisk forurensning inkludert tungmetaller som kvikksølv, samt meteorologiske parametre. Programmet omfatter også oppbyggingen av et luftflaskearkiv. Etter de første 6 månedene med den første Antarktisvinteren ser alle instrumenter ut til å være i meget god tilstand og levererkontinuerlig nye data. Disse analyseres for tiden, og de første resultatene vil bli publisert tidlig i 2008. Måleprogrammet finansieres i all hovedsak gjennom forskningsprogrammet NARE (Norwegian Antarctic Research Expeditions) ved Norsk polarinstitutt.
Keywords: Dronning Maud Land; Troll forskningsstasjon; miljøovervåking; målinger

FINAL Comprehensive Environmental Evaluation (CEE) for the upgrading of the Norwegian summer station Troll in Dronning Maud Land, Antarctica, to permanent station - Polarinstitutt, Norsk; Instituttet (Norwegian Polar Institute, 2004)
Keywords: Dronning Maud Land; forskningsstasjoner; miljøvern

Construction and operation of Troll Runway: initial environmental evaluation - Norsk Polarinstitutt; Polarinstitutt, Norsk (Norwegian Polar Institute, 2002)
Keywords: Dronning Maud Land; logistikk; luftfart

Antarctic Treaty: Report of the Norwegian antarctic inspection under article VII of the Antarctic Treaty ([Justis- og beredskapsdepartementet], 2001)
Article VII of the Antarctic Treaty entitles each Consultative Party to designate observers who shall have the right to carry out unannounced on-spot inspections. The purpose of these inspections is to promote the objectives of and ensure compliance with the provisions of the Antarctic Treaty and the easures adopted under it. The observers shall be accorded complete freedom of access at any time to all areas of Antarctica, including all stations within those areas, as well as vessels and aircrafts at points of embarkation and disembarkation. Article 14 of the Protocol on Environmental Protection to the Antarctic Treaty commit the Consultative Parties to undertake inspections under Article VII of the Antarctic Treaty in order to promote the protection of the Antarctic environment and dependent and associated ecosystems, and to ensure compliance with the Environmental Protocol.
Keywords: Antarktis; Norge; forskningsstasjoner